Sequences of coalition structures in multi-agent systems applied to disaster response - Rodrigues, Tabajara Krausburg (2022)
Coalition formation has long been an interesting topic of research in Multi-Agent Systems, either for its practical applications or complexity issues. A coalition is commonly understood as a short-lived and goal-directed structure, in which the agents join forces to achieve a goal. Cooperative game theory has been used as a formal mechanism to analyse the problem of grouping agents into coalitions. The problem is then modelled by a Characteristic-Function Game (CFG) in which the outcome is a coalition structure: a partition of agents into coalitions. However, not all problems can be effciently solved using a single coalition structure. For instance, one might be interested in a group hierarchy in which a coalition structure per level is required. In this thesis, we investigate coalition formation problems that are interdependent. In particular, we focus on the interdependence among solutions (i.e., coalition structures) produced by each game individually. Given the lack of work on this topic, we propose a novel game named Sequential Characteristic-Function Game (SCFG), which aims to model the relationships between subsequent coalition structures in a sequence of CFGs. We approach the resulting problem under both theoretical and practical perspectives. We extend the proposed game to allow fine-grained constraints being induced over each CFG in the sequence. Also, we show that the underlying SCFG problem is PSPACE-complete. From an algorithmic viewpoint, we propose an exact algorithm based on dynamic programming, as well as two heuristic algorithms to compute solutions for SCFG instances. We show that there exists a trade-off in choosing one algorithm over the others. Moreover, we model a disaster response operation that employs the incident command system framework, and we show how one can apply our proposed framework and algorithms to solve such an interesting problem.